„Praworządność na wygnaniu”, czyli o nieprzemijającej aktualności pewnego Homerowego porównania - Appel, Włodzimierz (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2023)
In one of his similes (Π 384–393), Homer noticed that Zeus is angry with people for breaking the law with unjust judgments (σκολιὰς κρίνωσι θέμιστας) and that was how they were driving justice away (ἐκ δὲ δίκην ἐλάσωσι). The author of the article compares this statement with observations made by Hesiod (Op. 224 sqq.), who devoted relatively great space to the issues of law and justice (Δίκη). Hesiod’s statements turn out to be timeless and are reflected even in the diagnosis of our contemporary political life. The author ends his considerations with a reminder of the myth of Dike in Aratus’ poem.